Bismuth ferrite-barium titanate-based lead-free energy-storage relaxor ferroelectric ceramic material as well as preparation method and application thereof

By introducing linear dielectric CLT into BF-BT-based ceramics to regulate its microstructure, the problems of low energy storage density and efficiency in BF-BT ceramics are solved, and high energy storage and mechanical performance are improved, suitable for the new generation of storage Energy devices and energy conversion systems.

CN119241225AActive Publication Date: 2025-01-03CHENGDU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411764149.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

BF-BT-based lead-free relaxation ferroelectric ceramic materials have large residual polarization strength, low breakdown field strength and poor mechanical properties, resulting in low energy storage density and efficiency, and service stability and reliability. The poor performance is also challenging to improve the thermal stability and frequency stability of energy storage.

Method used

By introducing linear dielectric Ca0.7La0.2TiO3 (CLT), the microstructure, phase structure and domain structure of bismuth ferroelectric ferroelectric ceramics, the third component solid solution method is used to synthesize a brand new multicomponent Solid solution lead-free energy storage relaxation ferroelectric ceramic material (1-x) (0.67BiFeO3-0.33BaTiO3)-xCa0.7La0.2TiO3, regulates grain size and forms polar nanomicro regions, and enhances the resistance to electric field breakdown of ceramics Ability and resistance to plastic deformation.

Benefits of technology

It significantly improves energy storage performance and mechanical properties. BF-BT-based lead-free relaxation ferroelectric ceramics obtain excellent recoverable energy storage density and high energy storage efficiency under small electric fields, and exhibits good thermal stability and frequency stability. Its mechanical hardness is suitable for the new generation of miniaturized, lightweight, high reliability and high stability energy storage devices and energy conversion systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241225A_ABST
    Figure CN119241225A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material and a preparation method and application thereof, and relates to the technical field of functional materials, the chemical formula of the bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material is (1-x) (0.67 BiFeO3-0. 33 BaTiO3)-xCa0. 7La0. 2TiO3, x = 0.25-0.40, and x represents the mole fraction. According to the preparation method, BF-BT lead-free relaxor ferroelectric ceramic is taken as a raw material, a linear dielectric Ca0. 7La0. 2TiO3 is introduced into BF-BT lead-free relaxor ferroelectric ceramic in a third component solid solution mode, a brand-new multi-component solid solution lead-free energy storage relaxor ferroelectric ceramic material: (1-x) (0.67 BiFeO3-0. 33 BaTiO3)-xCa0. 7La0. 2TiO3 is synthesized by adopting a traditional solid-phase reaction method, and the purpose of improving energy storage and mechanical properties is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material and a preparation method and application thereof. Background Art

[0002] At present, ceramic dielectric capacitors are widely used in energy storage devices and energy conversion systems due to their ultra-high power density, fast charge and discharge speed, long cycle life and good temperature stability, such as pulse / high-power power supply systems used in various IoT electronic devices, hybrid vehicles, weapons and equipment, etc. However, compared with other energy storage devices (such as batteries, electrochemical capacitors, etc.), the energy storage density of dielectric capacitors is relatively small and the energy storage efficiency is relatively low, which has become the main factor restricting its rapid development and large-scale application. In view of this, many different types of dielectric capacitor materials have been rapidly developed in recent years. At present, according to the law of the change of the polarization state of dielectric energy storage materials with the applied electric field, they can be divided into four types, namely linear dielectrics (LD), ferroelectrics (FE), antiferroelectrics (AFE) and relaxor ferroelectrics (RFE). Generally, linear dielectrics have high energy storage efficiency and breakdown resistance, but due to their relatively low maximum polarization strength, their use in high energy storage applications is limited. Ferroelectrics have a larger saturation polarization and moderate breakdown strength, but their large remanent polarization leads to lower energy storage density and reduced efficiency. Antiferroelectrics have a good energy storage density, but their low energy storage efficiency and large heat dissipation have always been factors that restrict their application and development. Relaxor ferroelectrics exhibit moderate anti-breakdown field strength, large maximum polarization and low remanent polarization, making them very suitable for high energy storage.

[0003] Among the many dielectric materials, bismuth ferrite (BiFeO3, BF) ceramics are a type of lead-free multiferroic material with excellent performance. Because it does not contain toxic lead elements and has a high Curie temperature (≈850℃), a large spontaneous polarization intensity (100µC / cm 2) and lower sintering temperature, it has received more attention in recent years. During the sintering process, BF ceramics often cause large leakage current and low breakdown electric field due to the volatilization of bismuth elements and the change of iron valence. Therefore, barium titanate (BaTiO3, BT) is often dissolved in BF ceramics to improve leakage current and breakdown electric field, thereby achieving the purpose of improving the electrical properties of BF-based ceramics. In addition, by regulating the content of BF and BT, a new type of bismuth ferrite-barium titanate (BF-BT) lead-free relaxor ferroelectric ceramic material can be synthesized. This type of relaxor ferroelectric has good energy storage density performance, and the body contains polar nano-microregions (PNRs), which makes this type of material have a lower hysteresis loop, corresponding to a higher energy storage efficiency. In addition, by introducing other dielectric chemicals into BF-BT lead-free relaxor ferroelectric ceramic materials, new materials with higher energy storage density can be formed, which have great application prospects in the field of energy storage. For example, the introduction of CaTiO3 into BF-BT lead-free relaxor ferroelectric ceramics can achieve higher energy storage performance under an applied electric field of 380 kV / cm ( W rec =5.03 J / cm 3 , η = 89.7%). For example, the introduction of Nd (Zn 0.5 Zr 0.5 )O3 can be realized under a smaller external electric field ( E =240 kV / cm) induced enhanced recoverable energy storage density W rec =2.45 J / cm 3 And moderate energy storage efficiency η = 72%.

[0004] Although BF-BT-based lead-free relaxor ferroelectric ceramic materials have good energy storage controllability, most of the BF-BT-based energy storage ferroelectric ceramics reported so far still show large residual polarization intensity and low breakdown field strength, resulting in low energy storage density and efficiency, and there are also challenges in improving energy storage thermal stability and frequency stability. In addition, BF-BT-based ferroelectric ceramics have large grain sizes and many defects, which show poor mechanical properties, and will also limit the service stability, reliability and life of the device in complex environments. Developing BF-BT-based lead-free relaxor ferroelectric ceramic materials with both high energy storage performance and high mechanical properties from a new perspective will be a necessary task for the miniaturization, lightweight, high reliability and high stability of energy storage devices and energy conversion systems in the new era. Summary of the invention

[0005] Based on the fact that the current BF-BT based energy storage ferroelectric ceramics still show large residual polarization intensity, low breakdown field strength and poor mechanical properties, resulting in low energy storage density, low efficiency and poor service stability and reliability, and improving energy storage thermal stability and frequency stability also faces challenges. The purpose of the present invention is to provide a bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material and its preparation method and application, by introducing a linear dielectric Ca 0.7 La 0.2 TiO3 (CLT) is used to regulate the microstructure, phase structure, domain structure and relaxivity of bismuth ferrite-barium titanate ferroelectric ceramics, so as to achieve the purpose of improving both energy storage performance and mechanical properties, and provide high-reliability candidate materials for the new generation of micro energy storage devices and energy conversion systems.

[0006] The present invention is achieved through the following technical solutions: In a first aspect, the present application provides a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, wherein the chemical formula of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material is (1- x )(0.67BiFeO3-0.33BaTiO3)- x Ca 0.7 La 0.2 TiO3, among which x =0.25~0.40, x represents the mole fraction. Specifically, x It can be 0.25 or 0.30 or 0.35 or 0.40.

[0007] The present invention uses the third component solid solution method to convert the linear dielectric Ca 0.7 La 0.2 TiO3 (CLT) is introduced into BF-BT lead-free relaxor ferroelectric ceramics, and a new multi-component solid solution lead-free energy storage relaxor ferroelectric ceramic material is synthesized by traditional solid phase reaction method: (1- x )(0.67BiFeO3-0.33BaTiO3)- x Ca 0.7 La 0.2 TiO3 (abbreviated as BF-BT- x CLT, x=0.25~0.40). The design aims to regulate the microstructure, phase structure, domain structure and relaxivity of BF-BT ceramics by solid solution of the third component, so as to achieve the purpose of improving energy storage and mechanical properties. The results show that the introduction of linear dielectric CLT can greatly reduce the grain size of the BF-BT ceramic material system and form polar nano-microregions PNRs with excellent kinetic characteristics, resulting in enhanced electric field breakdown resistance, relaxivity and resistance to plastic deformation of the ceramic material, thereby obtaining enhanced energy storage performance and mechanical properties. When x =0.30, the BF-BT-based lead-free relaxor ferroelectric ceramics achieved excellent recoverable energy storage density under a small electric field (390 kV / cm). W rec =5.47 J / cm 3 , Enhanced energy storage efficiency η = 72.26%, good thermal stability (25 to 100 °C) and frequency stability (1 to 500 Hz) and ultra-high mechanical hardness H v =6.9GPa; when x =0.40, the energy storage efficiency of BF-BT based lead-free relaxor ferroelectric ceramics η As high as 81.10%. These performance indicators far exceed the energy storage performance and mechanical properties of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems. This new BF-BT-based lead-free relaxor ferroelectric ceramic material with excellent energy storage performance and mechanical properties is expected to be used in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the energy and electronic devices of the new era and the development and progress of mankind.

[0008] In a second aspect, the present application provides a method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, comprising the following steps: (1) According to the chemical formula of bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, chemical reagents Bi2O3, Fe2O3, TiO2, La2O3, BaCO3 and CaCO3 are weighed to prepare powder; (2) Using the powder to form granules to prepare a disc embryo; (3) Debinding the wafer embryo; (4) sintering the debinding disc embryo to obtain a disc ceramic material; (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material (BF-BT- x CLT ceramics).

[0009] Furthermore, when preparing the powder in step (1), the weighed chemical reagent is first subjected to ball milling treatment, then dried, and then pre-calcined. After pre-calcination, it is ball milled again, and then the slurry is taken out and dried into powder.

[0010] Furthermore, the temperature during the pre-sintering treatment is controlled at 800°C~850°C, and the holding time is 2h~3h.

[0011] Furthermore, when preparing the disc embryo in step (2), polyvinyl alcohol binder is added to the obtained powder for stirring and granulation, and the granulation is followed by sieving and then tableting on a powder dry pressing machine.

[0012] Furthermore, the prepared disc embryo has a diameter of 12 mm and a thickness of 0.8 mm to 1.4 mm.

[0013] Furthermore, the debinding process in step (3) includes the following three stages: The first stage was to heat from room temperature to 120°C at a rate of 1°C / min and keep the temperature for 2h; The second stage was to heat up to 450℃ at a rate of 1℃ / min and keep the temperature for 4h; The third stage is to heat the temperature to 600℃ at a rate of 1℃ / min and keep it for 4h, then cool it naturally to room temperature.

[0014] Furthermore, in step (4), the wafer embryo is covered with powder by burying and sintering; the sintering temperature is 1040°C~1100°C, and the temperature is kept for 3 hours.

[0015] Furthermore, before electrode plating, the upper and lower surfaces of the ceramic material are first polished, and then the polished ceramic is cleaned and dried, a layer of silver paste is coated on the upper and lower surfaces of the dried ceramic sheet, and then it is placed in an oven for drying, and finally the ceramic is placed in a muffle furnace for silver sintering to obtain bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material (BF-BT- x CLT ceramics).

[0016] In a third aspect, the present application provides an application of a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, including application in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention obtains unique microstructural characteristics: by introducing linear dielectric CLT into BF-BT-based lead-free relaxor ceramics through the third component solid solution method, the rhombohedral phase can be effectively regulated ( R3C ) and pseudocubic phase ( Pm-3m) coexistence structure, destroying the long-range ordered ferroelectric domain structure, forming polar nano-microregions PNRs with excellent dynamic characteristics, which helps to increase the maximum polarization intensity, reduce the residual polarization intensity, and increase relaxation behavior. At the same time, the microstructure grain size of the ceramic is greatly reduced, and the defects and porosity are low, which greatly improves the ceramic's ability to withstand breakdown and resist mechanical plastic deformation, helps to improve energy storage and mechanical properties at the same time, and provides technical reference for the development of energy storage materials with high energy storage performance and high mechanical properties.

[0018] (2) The present invention achieves excellent energy storage performance: by introducing linear dielectric CLT into the BF-BT matrix, its optimal components x =0.30 Under a small electric field (390 kV / cm), the recoverable energy storage density ( W rec ) up to 5.47 J / cm 3 , energy storage efficiency ( η ) is as high as 72.26%; when x =0.40, the energy storage efficiency of BF-BT based lead-free relaxor ferroelectric ceramics η As high as 81.10%. This patent can provide a promising alternative material for energy storage devices and energy conversion systems in actual work, and is also expected to be applied to a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the energy and electronic devices of the new era and the development and progress of mankind.

[0019] (3) The present invention achieves enhanced energy storage stability: by introducing linear dielectric CLT into the BF-BT matrix, its optimal composition x =0.30 At the test frequency of 1-500 Hz, its energy storage performance maintains good stability. For example, the recoverable energy storage density only decreases by Δ W rec <4.2%, the energy storage efficiency is only reduced by Δ η <4.19%. At the test temperature of 25°C -100°C, its energy storage performance also maintained good stability. For example, the recoverable energy storage density only decreased by Δ W rec <12.54%, the energy storage efficiency is only reduced by Δ η <19.33%. The enhanced energy storage stability can lay the foundation for the long service life of ceramic materials.

[0020] (4) The present invention achieves ultra-high mechanical properties: by introducing linear dielectric CLT into the BF-BT based system, its optimal components x =0.30 shows excellent resistance to plastic deformation and obtains ultra-high mechanical hardness value Hv =6.9GPa. The ultra-high mechanical behavior can lay the foundation for the reliability and stability of ceramic materials in resisting external interference in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 In the present invention, BF-BT- x CLT ceramic technology roadmap and BF-BT- x Performance comparison of CLT ceramics and many lead-free energy storage ceramic materials; (a) is the technology roadmap, (b) is the BF-BT- x Performance comparison chart of CLT ceramics and many lead-free energy storage ceramic materials; Figure 2 In the embodiment of the present invention, BF-BT- x Crystal structure and domain structure of CLT ceramics; (a) BF-BT- x XRD patterns of CLT ceramics, (b) and (c) are local enlarged images of the (111) and (200) diffraction peaks in the XRD patterns, (d) is a TEM image; (e) is a PFM image; Figure 3 In the embodiment of the present invention, BF-BT- x Microstructure diagram of CLT ceramics; (ad) is BF-BT- x SEM micrograph of the thermally etched surface of CLT ceramics, with the inset being the grain size distribution; Figure 4 In the embodiment of the present invention, BF-BT- x Dielectric behavior and relaxation behavior diagram of CLT ceramics; (a) is BF-BT- x The dielectric temperature spectrum of CLT ceramics, (b) is the dielectric temperature curve fitted using the modified Curie-Weiss theorem; Figure 5 In the embodiment of the present invention, BF-BT- x Hysteresis curve and energy storage behavior diagram of CLT ceramics; (a) is BF-BT- x Hysteresis curves of CLT ceramics under different electric fields, (b) BF-BT- x The recoverable energy storage density and energy storage efficiency of CLT ceramics vary with the components; Figure 6In the embodiment of the present invention, BF-BT- x Frequency and temperature stability behavior diagram of CLT ceramics; (a) is the optimal composition x =0.30 Ceramic obtained at 1-500 Hz test frequency PE Curve, (b) is the polarization intensity, recoverable energy storage density and energy storage efficiency obtained at different test frequencies, (c) is the optimal component x =0.30 ceramics obtained at a test temperature of 25 ℃-100 ℃ PE Curve (d) is the recoverable energy storage density and energy storage efficiency obtained at different test temperatures; Figure 7 In the embodiment of the present invention, BF-BT- x Mechanical properties of CLT ceramics; (a) is the optimal component x =0.30 BF-BT based relaxor ferroelectric ceramics tested under different loads. (b) is the optimal component x =0.30 Vickers indentation scanning electron microscopy image of BF-BT based relaxor ferroelectric ceramics. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0023] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention uses the third component solid solution method to convert the linear dielectric Ca 0.7 La 0.2 TiO3 (CLT) is introduced into BF-BT lead-free relaxor ferroelectric ceramics to regulate the microstructure, phase structure, domain structure and relaxivity of BF-BT ceramics, and finally achieve the purpose of improving energy storage and mechanical properties. x =0.30, BF-BT-based lead-free relaxor ferroelectric ceramics achieve excellent recoverable energy storage density under small electric field (390 kV / cm). W rec =5.47 J / cm 3 , Enhanced energy storage efficiency η= 72.26%, good thermal stability (25 to 100 °C) and frequency stability (1 to 500 Hz) and ultra-high mechanical hardness H v =6.9GPa; when x =0.40, the energy storage efficiency of BF-BT based lead-free relaxor ferroelectric ceramics η As high as 81.10%. These performance indicators far exceed the energy storage performance and mechanical properties of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems. This new BF-BT-based lead-free relaxor ferroelectric ceramic material with excellent energy storage performance and mechanical properties is expected to be used in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the energy and electronic devices of the new era and the development and progress of mankind.

[0025] Among them, the prepared BF-BT- x The performance characterization method of CLT ceramics is: (1) BF-BT- x Structural characterization methods for CLT ceramics: X-ray diffractometer (XRD) was used to characterize the BF-BT- x The crystal structure and phase structure of CLT ceramics were characterized using Cu target Kα radiation over a test angle range (2 θ ) 20°-80°, the scanning speed was 2 ° / min. The BF-BT- x Domain size, domain distribution and domain structure characteristics of CLT ceramics. For TEM characterization, BF-BT- x CLT ceramics need to be mechanically polished first, and then thinned using an ion gun voltage of 5 kV on an ion thinning instrument. After a small hole is formed, the ion gun voltage is reduced to 3.5 kV and thinning is continued for 30 minutes to obtain a TEM sample. The surface microstructure of the ceramic sample after thermal etching was observed using a scanning electron microscope (SEM) and the average grain size of the sample was calculated. The BF-BT- x The domain size, domain distribution and domain structure characteristics of CLT ceramics are studied, and their piezoelectric response is analyzed.

[0026] (2) BF-BT- x Characterization methods of electrical and mechanical properties of CLT ceramics: Using high temperature dielectric thermometer to measure BF-BT- x The relationship between the dielectric constant and dielectric loss of CLT ceramics and temperature is tested at a temperature of 35°C to 450°C. The modified Curie-Weiss theorem is used to fit the dielectric-temperature curve to obtain BF-BT- xThe relaxation properties of CLT ceramics. The BF-BT- x Hysteresis of CLT ceramics ( PE ) curve, and the corresponding recoverable energy storage density ( W rec ) and energy storage efficiency ( η In addition, the BF-BT- x Hysteresis of CLT ceramics ( PE ) curve to analyze its frequency stability and temperature stability. x The load displacement curves and mechanical deformation of CLT ceramics under different loads (10 mN, 20 mN, 30 mN, 40 mN and 50 mN) were characterized, and the indentation morphology and mechanical deformation were analyzed using atomic force microscopy (AFM). x The mechanical deformation and hardness of CLT ceramics were characterized. The indentation load was 1.961 N and the load was maintained for 15 s. The Vickers hardness was calculated by measuring the average length of the indentation diagonal. Before performing nanoindentation and Vickers indentation tests, polishing treatment is required. x CLT ceramic surface. First use 1000 grit coarse sandpaper, then 4000 grit fine sandpaper, and finally use diamond particles to polish until it reaches the requirement of 0.05 µm.

[0027] BF-BT- x The specific implementation cases of CLT ceramics are as follows: Example 1

[0028] This embodiment provides a method for preparing a BF-BT-0.25CLT lead-free relaxor ferroelectric ceramic. The preparation process is as follows: Figure 1 As shown, follow these steps: S1. Prepare chemical reagents: Bi2O3(AR 99%), Fe2O3(AR 99%), TiO2(AR 99%), La2O3(AR99.9%), BaCO3(AR 99%) and CaCO3(AR 99%).

[0029] S2, the chemical reagents in step S1 are adjusted according to 0.75 (0.67BiFeO3-0.33BaTiO3)-0.25Ca 0.7 La 0.2TiO3 (BF-BT-0.25CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball mill jar and milled with anhydrous ethanol as the dispersion medium for 20-24 h using a planetary ball mill at a speed of 215 r / min to fully mix the chemical reagents.

[0030] S3. Take out the highly mixed BF-BT-0.25CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850 °C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.25CLT ceramic main crystal are obtained through solid phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215 r / min for 12-20 hours, and then the slurry is taken out and dried into powder.

[0031] S4. Add 7% polyvinyl alcohol (PVA) binder by mass fraction to the obtained BF-BT-0.25CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15 MPa, and the powder is molded into a BF-BT-0.25CLT disc embryo with a diameter of 12 mm and a thickness of 1 mm.

[0032] S5. The BF-BT-0.25CLT disc embryo is subjected to binder removal treatment in a muffle furnace. The binder removal temperature is set to rise from room temperature to 120°C at a heating rate of 1°C / min for 2 h, then rise to 450°C at a heating rate of 1°C / min for 4 h, and finally rise to 600°C at a heating rate of 1°C / min for 4 h, and then naturally cool to room temperature after insulation. Then, the BF-BT-0.25CLT disc embryo after binder removal is placed in a muffle furnace for sintering. Covering the disc embryo with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 h, and naturally cooled to room temperature, and finally the BF-BT-0.25CLT ceramic material is obtained.

[0033] S6. Polish the upper and lower surfaces of the BF-BT-0.25CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain a BF-BT-0.25CLT ceramic material that meets electrical testing and engineering applications.

[0034] The following performance characteristics were performed on the BF-BT-0.25CLT ceramic material prepared by the method of this embodiment.

[0035] 1) XRD and SEM were used to test the ceramic samples, proving that the linear dielectric 0.25CLT component was successfully introduced into the BF-BT lattice, and the ceramics showed a pure perovskite structure with a rhombohedral phase ( R3C ) and pseudocubic phase ( Pm-3m ) Two-phase coexistence structure ( Figure 2 At the same time, after introducing 0.25CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.70 μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0036] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced after the introduction of 0.25CLT component ( Figure 4 ), and obtain a larger relaxation fitting coefficient γ =1.90, which is beneficial to improving energy storage performance.

[0037] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density of the BF-BT-0.25CLT ceramic sample ( W rec ) and energy storage efficiency ( η ), where the recoverable energy storage density ( W rec ) is 2.89 J / cm 3 , energy storage efficiency ( η ) up to 72.8% ( Figure 5 ).

[0038] Example 2

[0039] This embodiment provides a method for preparing BF-BT-0.30CLT lead-free relaxor ferroelectric ceramics. The preparation process is as follows: Figure 1As shown, follow these steps: S1. Prepare chemical reagents: Bi2O3(AR 99%), Fe2O3(AR 99%), TiO2(AR 99%), La2O3(AR99.9%), BaCO3(AR 99%) and CaCO3(AR 99%).

[0040] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.70 (0.67BiFeO3-0.33BaTiO3)-0.30Ca 0.7 La 0.2 TiO3 (BF-BT-0.30CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball mill jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to ensure that the chemical reagents were fully mixed.

[0041] S3. Take out the highly mixed BF-BT-0.30CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850 °C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.30CLT ceramic main crystal are obtained through solid phase reaction. After pre-sintering, the powder is placed in a ball mill and ball milled on a planetary ball mill at a speed of 215 r / min for 12-20 hours, and then the slurry is taken out and dried into powder.

[0042] S4. Add 7% polyvinyl alcohol (PVA) binder by mass to the obtained BF-BT-0.30CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15 MPa, and the powder is molded into a BF-BT-0.30CLT disc embryo with a diameter of 12 mm and a thickness of 1 mm.

[0043] S5. The BF-BT-0.30CLT disc embryo is subjected to binder removal treatment in a muffle furnace. The binder removal temperature is set to rise from room temperature to 120°C at a heating rate of 1°C / min for 2 h, then rise to 450°C at a heating rate of 1°C / min for 4 h, and finally rise to 600°C at a heating rate of 1°C / min for 4 h, and then naturally cool to room temperature after insulation. Then, the BF-BT-0.30CLT disc embryo after binder removal is placed in a muffle furnace for sintering. Covering the disc embryo with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 h, and naturally cooled to room temperature, and finally the BF-BT-0.30CLT ceramic material is obtained.

[0044] S6. Polish the upper and lower surfaces of the BF-BT-0.30CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain a BF-BT-0.30CLT ceramic material that meets electrical testing and engineering applications.

[0045] The following performance characteristics were performed on the BF-BT-0.30CLT ceramic material prepared by the method of this embodiment.

[0046] 1) XRD was used to test the ceramic samples (using Cu target Kα radiation, test angle range (2 θ ) 20°-80°, scanning speed 2 ° / min), proving that the linear dielectric 0.30CLT component was successfully introduced into the BF-BT lattice, and the ceramic showed a pure perovskite structure with a rhombohedral phase ( R3C ) and pseudocubic phase ( Pm-3m ) Two-phase coexistence structure ( Figure 2 ). By observing the domain structure of the ceramic sample by TEM (accelerating voltage of 200 kV) and PFM, it was found that the ceramic body has uniformly distributed polar nano-microdomains PNRs ( Figure 2 ). Polar nano-microregion PNRs with excellent kinetic characteristics help to increase the maximum polarization intensity, reduce the residual polarization intensity and enhance the relaxation behavior, which is an important contribution to optimizing energy storage performance. At the same time, the ceramic samples were tested using SEM. After introducing 0.30CLT components into the matrix, it was found that the grain size of the ceramic samples was significantly reduced to 0.63 μm. The surface of the sample was very dense, with no obvious visible pores and defects ( Figure 3 ). Among them, BF-BT-0.30CLT ceramic material has the smallest grain size, which greatly improves the ceramic's ability to withstand breakdown and mechanical plastic deformation, and helps to improve both energy storage and mechanical properties.

[0047] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced by introducing 0.30CLT components ( Figure 4 ), and obtain a larger relaxation fitting coefficient γ =1.92. Among them, the BF-BT-0.30CLT ceramic material has the largest relaxation fitting coefficient, corresponding to the largest relaxation behavior, which helps to improve the energy storage performance.

[0048] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density of the BF-BT-0.30CLT ceramic sample ( W rec ) and energy storage efficiency ( η ). Among them, the recoverable energy storage density ( W rec ) up to 5.47 J / cm 3 , energy storage efficiency ( η ) up to 72.26% ( Figure 5 ), while the breakdown electric field is increased to 390kV / cm. Among all components, x=0.03 has the largest recoverable energy storage density and good energy storage efficiency. At the same time, this energy storage performance far exceeds the energy storage performance of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems ( Figure 1 ), can provide a promising alternative material for energy storage devices and energy conversion systems in actual work, and is also expected to be applied to a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the new era of energy and electronic devices as well as human development and progress.

[0049] 4) The energy storage performance of the BF-BT-0.30CLT ceramic sample maintained excellent stability at the test frequency of 1-500 Hz, and the recoverable energy storage density only decreased by Δ W rec <4.2%, the energy storage efficiency is only reduced by Δ η <4.19%. At the test temperature of 25℃-100℃, its energy storage performance also maintained good stability, and the recoverable energy storage density only decreased by Δ W rec <12.54%, the energy storage efficiency is only reduced by Δ η <19.33%( Figure 6 ). Excellent energy storage stability can lay the foundation for the long service life of ceramic materials.

[0050] 5) The mechanical properties of BF-BT-0.30CLT ceramic samples were tested using a nanoindenter and a Vickers indenter. The ceramic samples exhibited different deformation behaviors under different loads. The results showed that BF-BT-0.30CLT ceramics have good resistance to plastic deformation and have achieved ultra-high mechanical hardness. H v =6.9 GPa( Figure 7 ). The ultra-high mechanical behavior can lay the foundation for the reliability and stability of ceramic materials in resisting external interference in practical applications.

[0051] Example 3

[0052] This embodiment provides a method for preparing a BF-BT-0.35CLT lead-free relaxor ferroelectric ceramic. The preparation process is as follows: Figure 1 As shown, follow these steps: S1. Prepare chemical reagents: Bi2O3(AR 99%), Fe2O3(AR 99%), TiO2(AR 99%), La2O3(AR99.9%), BaCO3(AR 99%) and CaCO3(AR 99%).

[0053] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.65 (0.67BiFeO3-0.33BaTiO3)-0.35Ca 0.7 La 0.2 TiO3 (BF-BT-0.35CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball mill jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to ensure that the chemical reagents were fully mixed.

[0054] S3. Take out the highly mixed BF-BT-0.35CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850 °C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.35CLT ceramic main crystal are obtained through solid phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215 r / min for 12-20 hours, and then the slurry is taken out and dried into powder.

[0055] S4. Add 7% polyvinyl alcohol (PVA) binder by mass fraction to the obtained BF-BT-0.35CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15 MPa, and the powder is molded into a BF-BT-0.35CLT disc embryo with a diameter of 12 mm and a thickness of 1 mm.

[0056] S5. The BF-BT-0.35CLT disc blank is subjected to binder removal in a muffle furnace. The binder removal temperature is set to rise from room temperature to 120°C at a heating rate of 1°C / min for 2 h, then to 450°C at a heating rate of 1°C / min for 4 h, and finally to 600°C at a heating rate of 1°C / min for 4 h, and then naturally cool to room temperature after insulation. Then, the BF-BT-0.35CLT disc blank after binder removal is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 h, and naturally cooled to room temperature, and finally the BF-BT-0.35CLT ceramic material is obtained.

[0057] S6. Polish the upper and lower surfaces of the BF-BT-0.35CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain a BF-BT-0.35CLT ceramic material that meets electrical testing and engineering applications.

[0058] The following performance characteristics were performed on the BF-BT-0.35CLT ceramic material prepared by the method of this embodiment.

[0059] 1) XRD and SEM were used to test the ceramic samples, proving that the linear dielectric 0.35CLT component was successfully introduced into the BF-BT lattice, and the ceramics showed a pure perovskite structure with a rhombohedral phase ( R3C ) and pseudocubic phase ( Pm-3m ) two-phase coexistence structure, but at this time the pseudo cubic phase ( Pm-3m ) dominates ( Figure 2 At the same time, after introducing 0.35CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.65 μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0060] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced by introducing 0.35CLT components ( Figure 4 ), and obtain a larger relaxation fitting coefficient γ =1.84, which is beneficial to improving energy storage performance.

[0061] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density of the BF-BT-0.35CLT ceramic sample ( W rec ) and energy storage efficiency ( η ), where the recoverable energy storage density ( W rec ) is 2.51 J / cm 3 , energy storage efficiency ( η ) up to 79.22% ( Figure 5 ).

[0062] Example 4

[0063] This embodiment provides a method for preparing a BF-BT-0.40CLT lead-free relaxor ferroelectric ceramic. The preparation process is as follows: Figure 1 As shown, follow these steps: S1. Prepare chemical reagents: Bi2O3(AR 99%), Fe2O3(AR 99%), TiO2(AR 99%), La2O3(AR99.9%), BaCO3(AR 99%) and CaCO3(AR 99%).

[0064] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.60 (0.67BiFeO3-0.33BaTiO3)-0.40Ca 0.7 La 0.2 TiO3 (BF-BT-0.40CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball mill jar and milled with anhydrous ethanol as the dispersion medium for 20-24 h using a planetary ball mill at a speed of 215 r / min to ensure that the chemical reagents were fully mixed.

[0065] S3. Take out the highly mixed BF-BT-0.40CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850 °C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.40CLT ceramic main crystal are obtained through solid phase reaction. After pre-sintering, the powder is placed in a ball mill and ball milled on a planetary ball mill at a speed of 215 r / min for 12-20 hours, and then the slurry is taken out and dried into powder.

[0066] S4. Add 7% polyvinyl alcohol (PVA) binder by mass fraction to the obtained BF-BT-0.40CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15 MPa, and the powder is molded into a BF-BT-0.40CLT disc embryo with a diameter of 12 mm and a thickness of 1 mm.

[0067] S5. The BF-BT-0.40CLT disc blank is subjected to binder removal in a muffle furnace. The binder removal temperature is set to rise from room temperature to 120°C at a heating rate of 1°C / min for 2 h, then to 450°C at a heating rate of 1°C / min for 4 h, and finally to 600°C at a heating rate of 1°C / min for 4 h, and then naturally cool to room temperature after insulation. Then, the BF-BT-0.40CLT disc blank after binder removal is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 h, and naturally cooled to room temperature, and finally the BF-BT-0.40CLT ceramic material is obtained.

[0068] S6. Polish the upper and lower surfaces of the BF-BT-0.40CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain a BF-BT-0.40CLT ceramic material that meets electrical testing and engineering applications.

[0069] The following performance characteristics were performed on the BF-BT-0.40CLT ceramic material prepared by the method of this embodiment.

[0070] 1) Using XRD and SEM to test the ceramic samples, it was proved that the linear dielectric 0.40CLT component was successfully introduced into the BF-BT lattice, and the ceramic showed a pure perovskite structure. At this time, the crystal structure is a pseudo-cubic phase ( Pm-3m )structure( Figure 2 At the same time, after introducing 0.40CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.66 μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0071] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced after the introduction of 0.40CLT component ( Figure 4 ), and obtain a larger relaxation fitting coefficient γ =1.79, which is beneficial to improving energy storage performance.

[0072] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density of the BF-BT-0.40CLT ceramic sample ( W rec ) and energy storage efficiency ( η ). Among them, the recoverable energy storage density ( W rec ) is 2.63 J / cm 3 , energy storage efficiency ( η ) up to 81.10% ( Figure 4 Among all the components, x =0.40, the BF-BT based relaxor ferroelectric ceramic material has the highest energy storage efficiency.

[0073] Based on the above test results, the optimal group in this case is x =0.30, from Figure 3 It can be seen that with the introduction of CLT, the BF-BT-based ceramics are extremely dense and the grain size is greatly reduced, with an average grain size of about 0.63~0.70 um. x =0.30 The grain size is the smallest, which helps to improve the material's ability to withstand breakdown, thus directly affecting the energy storage performance of the ceramic. At the same time, the reduction in grain size and the densification of the organizational structure can increase its hardness value, which is of great help in optimizing mechanical properties. Figure 4 The optimal component can be seen in x =0.30, the relaxor ferroelectric ceramic has the largest relaxation fitting coefficient γ =1.92, indicating the maximum relaxation behavior. Figure 5 It can be seen that for the optimal component x =0.30, and obtained excellent recoverable energy storage density ( W rec =5.47 J / cm 3 ) and energy storage efficiency ( η =72.26%)); when x =0.40, the energy storage efficiency of BF-BT based lead-free relaxor ferroelectric ceramics η As high as 81.10%. Figure 6 It can be seen that the optimal component x=0.30, the recoverable energy storage density of the relaxor ferroelectric ceramics only decreased by Δ W rec <4.2%, the energy storage efficiency is only reduced by Δ η <4.19%, indicating excellent frequency stability. x =0.30, the recoverable energy storage density of the relaxor ferroelectric ceramics decreased by only Δ W rec <12.54%, the energy storage efficiency is only reduced by Δ η <19.33%, indicating that it has good temperature stability. Figure 7 It can be seen that the optimal component x =0.30 BF-BT based relaxor ferroelectric ceramics have different mechanical deformation and maximum indentation depth under different loads. The inset is the indentation morphology and plastic deformation behavior obtained under AFM test, and the indentation depth is 318 nm. x =0.30 BF-BT based relaxor ferroelectric ceramic Vickers indentation scanning electron microscopy image shows that the sample is subjected to a force of 1.961N and held for 15 s. The final hardness of the ceramic is calculated to be H v =6.9 GPa.

[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, characterized in that: The chemical formula of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material is (1- x )(0.67BiFeO3-0.33BaTiO3) - x Ca 0.7 La 0.2 TiO3, among which x =0.25~0.40, x Indicates the mole fraction.

2. A method for preparing the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 1, characterized in that: The following steps are involved: (1) According to the chemical formula of bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, chemical reagents Bi2O3, Fe2O3, TiO2, La2O3, BaCO3 and CaCO3 are weighed to prepare powder; (2) Using the powder to form granules to prepare a disc embryo; (3) Debinding the wafer embryo; (4) sintering the debinding disc embryo to obtain a disc ceramic material; (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material.

3. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: When preparing the powder in step (1), the weighed chemical reagent is first ball-milled, then dried, and then pre-calcined. After pre-calcination, it is ball-milled again, and then the slurry is taken out and dried into powder.

4. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 3, characterized in that: The temperature during the pre-firing treatment is controlled at 800℃~850℃, and the insulation time is 2h~3h.

5. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: When preparing the disc embryo in step (2), polyvinyl alcohol binder is added to the obtained powder for stirring and granulation. After granulation, the powder is sieved and then pressed into tablets on a powder dry pressing machine.

6. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 5, characterized in that: The diameter of the prepared disc embryo is 12 mm and the thickness is 0.8 mm to 1.4 mm.

7. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: The debinding process in step (3) includes the following three stages: The first stage was to heat from room temperature to 120°C at a rate of 1°C / min and keep the temperature for 2h; The second stage was to heat up to 450℃ at a rate of 1℃ / min and keep the temperature for 4h; The third stage is to heat the temperature to 600℃ at a rate of 1℃ / min and keep it for 4h, then cool it naturally to room temperature.

8. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: In step (4), the wafer embryo is covered with powder by buried firing; the sintering temperature is 1040°C~1100°C, and the temperature is kept for 3 hours.

9. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: Before electrode plating, the upper and lower surfaces of the ceramic material are first polished, and then the polished ceramic is cleaned and dried. A layer of silver paste is coated on the upper and lower surfaces of the dried ceramic sheet, and then it is placed in an oven to dry. Finally, the ceramic is placed in a muffle furnace for silver sintering to obtain a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material.

10. An application of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 1 or the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Including applications in energy storage devices and energy conversion systems.

Citation Information

Patent Citations

  • Ceramic capacitor material and preparation method thereof

    CN114436646A

  • Bismuth ferrite-based lead-free ferroelectric ceramic material with high Curie temperature and energy storage characteristic and preparation method of bismuth ferrite-based lead-free ferroelectric ceramic material

    CN115385675A

  • Sodium bismuth titanate-based relaxor ferroelectric ceramic material with excellent energy storage performance and environmental stability and preparation method of sodium bismuth titanate-based relaxor ferroelectric ceramic material

    CN116444265A

  • Dielectric ceramic material, dielectric ceramic layer, preparation method of dielectric ceramic material and dielectric ceramic layer, and capacitor

    CN117637344A

  • Lead-free high-entropy ferroelectric ceramic material as well as preparation method and application thereof

    CN117735974A